Age-Related Declines in Early Sensory Memory: Identification of Rapid Auditory and Visual Stimulus Sequences - Fogerty, Daniel; Humes, Larry E.; Busey, Thomas A. (Frontiers in Aging Neuroscience, 2016)
Age-related temporal-processing declines of rapidly presented sequences may involve contributions of sensory memory. This study investigated recall for rapidly presented auditory (vowel) and visual (letter) sequences presented at six different stimulus onset asynchronies (SOA) that spanned threshold SOAs for sequence identification. Younger, middle-aged, and older adults participated in all tasks. Results were investigated at both equivalent performance levels (i.e., SOA threshold) and at identical physical stimulus values (i.e., SOAs). For four-item sequences, results demonstrated best performance for the first and last items in the auditory sequences, but only the first item for visual sequences. For two-item sequences, adults identified the second vowel or letter significantly better than the first. Overall, when temporal-order performance was equated for each individual by testing at SOA thresholds, recall accuracy for each position across the age groups was highly similar. These results suggest that modality-specific processing declines of older adults primarily determine temporal-order performance for rapid sequences. However, there is some evidence for a second amodal processing decline in older adults related to early sensory memory for final items in a sequence. This selective deficit was observed particularly for longer sequence lengths and was not accounted for by temporal masking.